Electronic Commerce, Ninth Edition - Schneider, Gary P. (Course Technology, 2012)
E-commerce continues to have a dramatic impact on virtually every aspect of business. And following the Global Economic Crisis, its role is even more critical. Packed with the most cutting-edge coverage available, ELECTRONIC COMMERCE, 9e equips students with a solid understanding of the dynamics of this fast-paced industry. It delivers comprehensive coverage of emerging online technologies and trends and their influence on the electronic commerce marketplace. By detailing how the landscape of online commerce is evolving, this market-leading text reflects changes in the economy and how business and society are responding to those changes. Balancing technological issues with the strategic business aspects of successful e-commerce, the new edition includes expanded coverage of international issues, social networking, mobile commerce, Web 2.0 technologies, and updates on spam, phishing, and identity theft.